RICHARD SEARS: AMERICAN «SUCCESS STORY» - Tatiana Victorovna Pantyukhina (Вестник Северо-Кавказского федерального университета)
The article deals with the career of an American businessman of the turn of the XX-th century Richard Sears. His life and career personify the idea of success held by Americans.